Perceptual bias in Gestalt grouping by proximity affected by visual working memory load - Aybora Koç; Aleksandar Bulajić; Antonino Esposito; Thomas Lachmann; Cees van Leeuwen (Acta Psychologica, 2025)
Basic perceptual processes, including perceptual grouping, are subject to bias. Bias for cardinal orientations interferes with Gestalt grouping by proximity in dot lattices. A critical question is whether the bias arises in perceptual encoding or rather is conveyed in a top-down fashion, possibly mediated by visual working memory. Consistent with the latter, the load and content of Visual Working Memory (VWM) modulate the orientation bias strength (Esposito et al., 2023). These authors adopted a design that closely followed the classical dot-lattice studies. This inevitably confounded VWM load and the perceptual complexity of the stimuli stored in VWM. We used a highly simplified design that allows for the separation of VWM and perceptual load effects. The design varies VWM load by introducing an N-back task and uses flanker congruency to independently vary perceptual load. Results suggest that the intrusion of perceptual bias into grouping by proximity depends on VWM load rather than on perceptual load. The results dissociate perceptual orientation bias from psychophysical orientation bias, suggesting that psychophysical models of bias do not generalize to perceptual bias due to the intrusion of systematic top-down effects.